2009
DOI: 10.1097/ta.0b013e318173f81e
|View full text |Cite
|
Sign up to set email alerts
|

Small Catheter Tube Thoracostomy: Effective in Managing Chest Trauma in Stable Patients

Abstract: SCTT is effective in managing chest trauma. It is comparable with LCTT in stable trauma patients. This study supports adopting image-guided small catheter techniques in the management of chest trauma in stable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…Rivera et al 20 conducted the study similar to ours and reported 131 PCs series in a trauma setting over a period of 3.5 years; they concluded that PCs are effective in managing chest trauma. However, in our series, PCs were placed by a member of our trauma team at the bedside and early after injury; in contrast, in the study by Riviera et al, PCs were placed in the radiology suite and in a somewhat delayed fashion (average, 5.5 days after injury).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Rivera et al 20 conducted the study similar to ours and reported 131 PCs series in a trauma setting over a period of 3.5 years; they concluded that PCs are effective in managing chest trauma. However, in our series, PCs were placed by a member of our trauma team at the bedside and early after injury; in contrast, in the study by Riviera et al, PCs were placed in the radiology suite and in a somewhat delayed fashion (average, 5.5 days after injury).…”
Section: Discussionsupporting
confidence: 49%
“…However, all of our PCs complications have been prospectively collected, including the failure rate. Like Rivera et al study, 20 we could not prove the benefit that PC has less tube-related pain, PC may require less pain medication, or whether their use translates into a better outcome such as shorter ICU and hospital stay. Our PCs were placed at the bedside and did not require transporting patient to the radiology suite or to specialists; thus, our practice may be more applicable to general hospital condition and may be associated with less cost.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, there is little evidence to support large-bore drains' superiority over small-bore drains. In fact, several studies suggest that smaller drains, as small as 10–14 F,11 may be as effective as larger drains in resolving traumatic haemothoraces, without significant differences in terms of the amount drained or length of time the drain remains in situ 11–15. Small-bore drains may also be better tolerated by the patient 16.…”
Section: Discussionmentioning
confidence: 99%
“…Pigtail catheters are frequently used in the paediatric population, as well as in adult, non‐traumatic situations. Only a few studies have considered pigtail catheter placement in injured adult patients, with placement usually performed by interventional radiologists rather than by trauma surgeons at the bedside.…”
Section: Introductionmentioning
confidence: 99%